Dispute Resolution Model for Granting Hareuta Peunulang through the Customary Court in Pidie Regency, Aceh Province - Aufa Miranti; Teuku Muttaqin Mansur; Sulaiman Sulaiman; Faridah Jalil (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2022)
Hareuta peunulang is a grant of immovable property from parents to their daughters before marriage in Pidie Regency, Aceh Province. Disputes are resolved through customary court, but the settlement that should have been settled at the mukim level was brought to the Mahkamah Shar'iyyah. Therefore, this study aimed to identify the causes of the hareuta peunulang practice disputes and find an effective and efficient model for resolving them through customary courts. Empirical juridical methods were used with data collected data through observation and interviews and analyzed using a qualitative descriptive approach. The results showed that disputes are caused by the lack of deliberation in the hareuta peunulang process. The social plurality of laws makes the dispute resolution model through customary courts ineffective and inefficient. Therefore, the role of the village head (keuchick) and head of mukim (imuem mukim) is needed to educate the community regarding customary justice procedures that should to conducted at the village (gampong) and mukim levels.